Compassion - a paradox in art and society - Boomgaard, Jeroen 1953- (Valiz, 2017)
'Compassion, A Paradox in Art and Society', is developed in close collaboration with artist Rini Hurkmans, initiator of the conceptual art work 'the Flag of Compassion'. The book aims to show what space an artwork can occupy in the public domain, and in a network of philosophical notions, art theory, societal institutions, collective identity formation and individual experience. Through its hybrid character it wants to form a case study for a new form of art analysis. Simultaneously, it deals with the social effectivity of art and questions how art nowadays can be relevant on a social and political level
Met index, literatuuropgave
Keywords: Kunst; Rezeption; Gesellschaft; Mitgefühl -- Motiv